Hul'q'umi'num' language heroes: a successful collaboration between Elders, community organisations, and Canadian West Coast universities. Issue 3 (3rd July 2019) - Sadeghi-Yekta, Kirsten
ABSTRACT: Community collaboration is essential to the survival of theatre and performance labour in the neoliberal university. This evidentiary document describes one project of a successful collaboration between Hul'q'umi'num' Elders and teachers, community organisations, and a range of Canadian West Coast universities, including the University of Victoria, Simon Fraser University and Royal Roads University. It will discuss how university-based theatre and performance work, applied in the community, can support the sustainability of Indigenous languages on Vancouver Island and beyond – and can thus make important contributions to community learning and survivance.